FUNCTIONAL CROWN LENGTHENING AS A PRE-RESTORATIVE PROCEDURE IN THE AESTHETIC ZONE - Nursolihati Vidya; Osa Amila Hafiyyah (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2024)
Introduction: Crown lengthening is a surgical procedure to increase the height of the clinical crown for aesthetic and restorative purposes, or combination. The indications include treatment of subgingival caries and altered passive eruption. Functional crown lengthening for restorative purposes in the esthetic zone should consider the concept of biologic width and the ideal proportion of the dentogingival complex. Case: A 39-year-old male patient was referred from the Department of Conservative Dentistry, RSGM UGM Prof. Soedomo to expose the maxillary anterior teeth crowns for full crown and veneer restorations. Clinical examination showed 11, 12, and 12 post root canal treatment with 3-4 mm remaining crowns. Teeth 13, 21, 22, and 23 appear short, excessive gingival display of 3 mm, with a diagnosis of altered passive eruption type 1B. Treatment: Functional crown lengthening was performed by gingivectomy followed by flap elevation, ostectomy, and osteoplasty. A fenestration was found at the apical of 22 and treated with regenerative procedure. Full crowns and veneers insertion was done 3 months after surgery. Crown lengthening as a pre-restorative procedure is a multidisciplinary treatment that considers the need for restoration by re-establishing the biologic width, to prevent inflammation and bone loss. In addition, adequate post- surgical tissue healing time prior to restoration is necessary to avoid gingival margin rebound and to assure long-term success of the restoration. Conclusionn : Functional crown lengthening as a pre-restorative procedure in the esthetic zone can gives satisfactory and stable results, with careful examination and correct surgical procedure.